2005
DOI: 10.1128/jvi.79.7.4238-4245.2005
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus X Protein Stimulates Viral Genome Replication via a DDB1-Dependent Pathway Distinct from That Leading to Cell Death

Abstract: The hepatitis B virus (HBV) X protein (HBx) is essential for virus infection and has been implicated in the development of liver cancer associated with chronic infection. HBx can interact with a number of cellular proteins, and in cell culture, it exhibits pleiotropic activities, among which is its ability to interfere with cell viability and stimulate HBV replication. Previous work has demonstrated that HBx affects cell viability by a mechanism that requires its binding to DDB1, a highly conserved protein imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
162
3
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 152 publications
(186 citation statements)
references
References 46 publications
19
162
3
2
Order By: Relevance
“…It has been demonstrated that HBx action on viral replication may be dependent to modulation of calcium homeostasis, which provides novel clues for HBx biology (Bouchard et al, 2001(Bouchard et al, , 2003Choi et al, 2005). In addition, HBx interactions with the proteasome complex or DDB1 and HBx activation of Src tyrosine kinases have also been reported to participate in the regulation of HBV replication (Klein et al, 1999;Zhang et al, 2004;Leupin et al, 2005).…”
Section: Hbxmentioning
confidence: 99%
“…It has been demonstrated that HBx action on viral replication may be dependent to modulation of calcium homeostasis, which provides novel clues for HBx biology (Bouchard et al, 2001(Bouchard et al, , 2003Choi et al, 2005). In addition, HBx interactions with the proteasome complex or DDB1 and HBx activation of Src tyrosine kinases have also been reported to participate in the regulation of HBV replication (Klein et al, 1999;Zhang et al, 2004;Leupin et al, 2005).…”
Section: Hbxmentioning
confidence: 99%
“…Green fluorescent protein (GFP), GFP-HBx, and GFP-HBx(R96E) expressed from EBS-PL 7 and from the lentiviral vector pWPTS, 6 and HA-DDB1 7 and myc-HBx 9 produced from pSRS have been described. Myc-HBx(R96E) was constructed by replacing the region encoding wild-type HBx in pSRS.…”
Section: Methodsmentioning
confidence: 99%
“…The HBx(R96E)-DDB1 and HBx(R96E)-DDB1(i947) fusions were expressed from EBS-PL. 9 The replicationcompetent, greater-than-unit-length wild-type HBV genomic DNA (payw1.2) and the HBx-deficient derivative (payw*7) 6 were recloned into pBluescript (Stratagene) upstream of a GFP gene derived from pEGFP-N1 (Clontech). Details of the constructs will be provided on request.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] The HBx protein of Hepatitis B virus (HBV) is also known to bind DDB1 possibly to facilitate viral replication by extending the S phase of cell cycle. 18,19 Further, HBx is shown to stabilize c-Myc by disrupting the SCF Skp2 complex and interfering with its ubiquitination. 20 Although both TRUSS and Skp2 regulate the intracellular levels of c-Myc, it is not clear if both regulators work in synergy or act sequentially during different phases of the cell cycle.…”
Section: Introductionmentioning
confidence: 99%